GAMIFICATION: AN EDUCATIONAL STRATEGY TO INCREASE STUDENTS’ MOTIVATION AND ACADEMIC PERFORMANCE - Atoyebi, Temitope Olufunmi; Olayiwola, Joy Oluwabukola; Eru, Akwuma Nathaniel; Kolapo, Ridwan; Kirubakaran, Prema (FUDMA Journal of Sciences, 2025)
In the era of Artificial Intelligence (AI), the educational system requires transformation, particularly in enhancing students’ critical thinking skills. Well-designed games can serve as an effective strategy for stimulating Higher-Order Thinking Skills (HOTS). In Nigerian universities, students often struggle with complex concepts, especially fresh undergraduates navigating their academic journey. However, most courses taught are designed in theories and practicals as the primary medium of instruction, there is a need for additional strategies to enhance students’ learning experiences. This paper explores the definition, history, benefits, and challenges of gamification in academic settings. By incorporating elements such as points, leaderboards, and badges, educators can foster a more engaging and motivating learning environment. The study argues that gamification simplifies complex concepts, aids retention, and enhances student engagement. Through a literature review, this paper examines how gamification can help students grasp difficult and voluminous tasks, the significance of its application, and its practical implications in higher education. Additionally, it addresses the challenges lecturers face in implementing gamification in the classroom. The findings demonstrate that gamification has the potential to improve student’s motivation, inspiration, engagement, and academic performance in university settings